Tubos de Ceriantharia (Cnidaria; Anthozoa): uma habitação marinha. De sua construção a seus inquilinos - Ceriello, Hellen [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
This study assessed marine biodiversity of microbes and metazoans found in ceriantharian tubes via species characterization, using both species traditional recognition and metagenomics of environmental DNA (eDNA) methods, and it also described ceriantharian tube-building behavior patterns. Using the traditional method for species characterization, 14 taxa of crustaceans were identified, including one novel species, Podocerus carmelina sp. nov., found in Ceriantheomorphe brasiliensis tubes (Mello-Leitão, 1919) (n = 3) and in unidentified tubes (n = 5). Also, two new location records for previously known crustacean species were reported as well as an identification key for Podocerus species with type localities in the Atlantic Ocean was provided. Analyses of eDNA metagenomics in tubes of C. brasiliensis (n = 2) and Ceriantheopsis lineata Stampar, Scarabino, Pastorino & Morandini, 2015 (n = 2) showed that these ceriantharian tubes are composed of 79% microbial families and 21% metazoan families. Moreover, tubes from different locations presented a higher metazoan diversity than the microbial that nearly remained unaltered, indicating that, although microbial families are abundant in ceriantharian tubes, they are uniform throughout different locations. The ceriantharian tube-building research revealed that Botrucnidifer norvegicus Carlgren, 1912 can build ramified tubes housing two polyps, adult C. brasiliensis lacks substrate selection mechanisms and sediment capture, is able to build more than a single tube throughout life, usually vertically oriented, and its behavior may differ from the species Isarachnanthus nocturnus (den Hartog, 1977) and Cerianthus vogti Danielssen, 1890. The ceriantharian tube is critical in controlling the internal water pressure in ceriantharians in addition to providing protection. In conclusion, this research demonstrated that, other than biodiverse microhabitats, ceriantharian tubes are potential tools for basic research and biodiversity surveys, driving studies of ecology, behavior, life cycles and cnidae toxicity.

Este estudo avaliou a biodiversidade marinha de micróbios e metazoários encontrados em tubos ceriantários por meio da caracterização de espécies, usando tanto o método de reconhecimento tradicional de espécies quanto o de metagenômica de DNA ambiental (eDNA), e também descreveu padrões de comportamento de construção de tubos ceriantários. Utilizando o método tradicional de caracterização de espécies, foram identificadas 14 taxa de crustáceos, incluindo uma nova espécie, Podocerus carmelina sp. nov., encontrados em tubos de Ceriantheomorphe brasiliensis (Mello-Leitão, 1919) (n = 3) e em tubos não identificados (n = 5). Além disso, foram relatados dois novos registros de localização para espécies de crustáceos anteriormente conhecidas, e uma chave de identificação para espécies de Podocerus com localidades-tipo no Oceano Atlântico foi proposta. Análises de metagenômica de eDNA em tubos de C. brasiliensis (n = 2) e Ceriantheopsis lineata Stampar, Scarabino, Pastorino & Morandini, 2015 (n = 2) mostraram que esses tubos ceriantários são compostos por 79% de famílias microbianas e 21% por famílias de metazoários. Além disso, tubos de diferentes localidades apresentaram maior diversidade de metazoários do que de micróbios que quase permaneceram inalterados, indicando que, embora famílias microbianas sejam abundantes nos tubos ceriantários, são uniformes em diferentes locais. O estudo sobre construção de tubos ceriantários revelou que Botrucnidifer norvegicus Carlgren, 1912 pode construir tubos ramificados abrigando dois pólipos, C. brasiliensis adulto não possui mecanismos de seleção de substrato e captura de sedimentos, é capaz de construir mais de um único tubo ao longo da vida, geralmente com orientação vertical, e seu comportamento pode diferir do das espécies Isarachnanthus nocturnus (den Hartog, 1977) e Cerianthus vogti Danielssen, 1890. Além de fornecer proteção, o tubo ceriantário é vital no controle de pressão interna da água em ceriantários. Em conclusão, esta pesquisa demonstrou que, além de microhabitats biodiversos, os tubos ceriantários são ferramentas potenciais para pesquisa básica e levantamentos de biodiversidade, impulsionando estudos de ecologia, comportamento, ciclos de vida e toxicidade de cnidas.
Tubes of Ceriantharia (Cnidaria; Anthozoa): a marine habitation. From its construction to its guests
Keywords: Behavior; Bioconstruction; eDNA; Marine biodiversity; Metagenomics; Microhabitat; Bioconstrução; Biodiversidade marinha; Comportamento; Metagenômica